At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

S+2t=6. 3s-2t=2
Using elimination


Sagot :

Ematio
For the first one, I will solve for t.
s + 2t = 6, first we isolate the t variable,
2t = -s + 6, divide both sides by 2,
t = -s/2 + 3, < There's your answer for 1!

Here's the second one,
3s - 2t = 2, subtract 3s from both sides,
-2t = 2 - 3s, divide both sides by -2,
t = -1 + 3s/2 < There's your second answer!